Penerapan Algoritma Naive Bayes dan Aplikasi RadipMiner Untuk Penentuan Status Gizi Balita - Jon Idrison Molina (Riau Jurnal Teknik Informatika, 2025)
Determining the nutritional status of toddlers is an important activity carried out by medical personnel at the health center as technical implementers. Because with the results of determining the nutritional status, intervention efforts to overcome the condition of toddlers who are in a status other than good nutrition can be overcome as early as possible. However, medical personnel often have difficulty in determining the nutritional status of toddlers due to limited human resources and equipment, so it is important to have a method used to determine the nutritional status of children under five years old quickly and accurately. For this reason, in this study we used the naïve Bayes algorithm in calculating the classification of determining the nutritional status of toddlers. The results of the study showed that the naïve Bayes algorithm can increase the level of data accuracy in determining the nutritional status of toddlers with a data accuracy value of 70.33%.